2015
DOI: 10.1097/mib.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Video Capsule Endoscopy of the Small Bowel for Monitoring of Crohnʼs Disease

Abstract: Video capsule endoscopy has revolutionized our ability to visualize the small bowel mucosa. This modality is a valuable tool for the diagnosis of suspected small bowel Crohn's disease, and it is increasingly used for the monitoring of disease activity in patients with established small bowel Crohn's. The purpose of the current article was to review the literature pertaining to the utilization of capsule endoscopy in established Crohn's disease, for monitoring of mucosal healing, postoperative recurrence, disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…As the SB is involved in over 70% of CD patients, its thorough evaluation is vital for initial diagnosis, establishing disease phenotype, and assessment of mucosal healing and prognosis [31][32][33]. Previous work has shown that CE was superior to CTE and SBFT, but not MRE [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the SB is involved in over 70% of CD patients, its thorough evaluation is vital for initial diagnosis, establishing disease phenotype, and assessment of mucosal healing and prognosis [31][32][33]. Previous work has shown that CE was superior to CTE and SBFT, but not MRE [3].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic modalities evaluated in our meta-analysis are all well-established and extensively evaluated for detection and follow-up of small bowel Crohn's disease .The current ECCO/ESGAR guidelines support the use of MRE, US and CE for these purposes, although evaluation of small bowel patency is required before utilization of CE in established CD [35]. The main purposes of diagnostic evaluation in established CD are validation of disease characteristics, establishement of prognosis, monitoring of mucosal healing and identification of complications [7,20,31,32,[38][39][40][41]. All the evaluated diagnostic modalities have their distinct diagnostic strengths and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrated that serial CE was well tolerated and was not associated with AEs for the evaluation of small-bowel CD. Several studies have shown that CE is a valid and reliable modality for the assessment of CD 33 and impacts clinical decision-making. 34 Two cross-sectional studies have shown that CE is a valid tool for the assessment of small-bowel CD, relative to magnetic resonance enterography, smallintestinal US, barium small-bowel follow-through, and colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study, Hall and colleagues showed that CECDAI was able to demonstrate mucosal healing of 27% and 62% of subjects initiating thiopruines or anti-TNF therapy based on a post-treatment score of <3–5 36 . The principle limitation of VCE is the potential for capsule retention due to stricturing disease, which despite the use of a patency capsule is reported to occur in 1.5–7.5% of all studies 37 . Further, without confirmative histology some lesions detected by VCE may be the result of alternative diagnoses such as non-steroidal-induced enteropathy.…”
Section: Capsule Endoscopy and Deep Enteroscopymentioning
confidence: 99%